Rationalization of using practical action research method in course development for entrepreneurship training programme - Amir Hussin, Muhammad Rosni (2018)
It is crucial for each study to justify the use of the action research method in their study. The decision to use action research approach begins with thinking carefully about justifying the choice because the researcher needs to argue the case clearly and cogently. Early justification is very important because action research is a flexible and responsive approach, where each spiral turn is an opportunity to learn, change, critique or improve the methodology. If the researchers are successful in justifying the use of action research, they can improve the research situation, and at the same time, improve their personal and professional skills. This paper will define action research and explain briefly three (3) categories of action research; practical, emancipatory, technical. As the focus, this paper next discusses action research paradigm in the field of entrepreneurship training course development. Finally, this paper will justify the appropriateness of using practical action research method to improve or to develop course for entrepreneurship training programme.